An Analysis of Monitoring and Evaluation System Launched by Punjab Education Department - Hamid Ali Nadeem, Azhar Mumtaz Saadi (JELM, 2023)
This study aimed to achieve following objectives: to analyze the monitoring and evaluation system of Punjab Education Department (Pakistan); to identify prevailing monitoring and evaluation practices in Punjab. The study was delimited to secondary schools of public sector in Punjab. Using multistage sampling technique, a sample of 32 head teachers, 320 teachers, 32 monitoring and evaluation assistants (MEAs) and 110 students was selected. Two questionnaires were developed for head teachers, teachers, and MEAs. The questions were asked about different dimensions of practices of monitoring & evaluation system. Three open ended questions were also added to enlist strong areas, weak areas and suggestions to improve the system. Data from the students was collected through group interviews by the researcher. Descriptive statistics was used for data analysis. Findings revealed that MEAs and Head teachers were fully aware about all monitoring indicators. Attendance and uniforms were maintained regularly to get minimum level of acceptable indicator. MEAs checked homework copies, cleanliness, uniform, textbooks. Suggestions included surprise visit after first scheduled visit, enhancement of remuneration for MEAs, joint meetings of monitoring staff and education department.